2006
DOI: 10.1080/15287390500362279
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute and Chronic Moderate Red or White Wine Consumption on Fasted and Postprandial Lipemia in the Rat

Abstract: The effects of acute and chronic (10 wk) red or white wine consumption on fasted and postprandial lipemia in the rat model are reported. Fasted rats, in the acute study, were loaded intragastrically with 5 ml of an olive oil emulsion (30% w/v) in the presence or absence of wine (8% v/v ethanol), and either mesenteric lymph or blood was collected 3 h postprandially. Animals in the chronic study received either red or white wine in drinking water for a period of 10 wk (3% v/v ethanol). Blood samples were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…The results of biochemical assays depicted in Table 2 demonstrated that in RW‐treated rats, the plasma levels of triglycerides, total cholesterol, and HDL were increased but without statistical significance, when compared to C group. Interestingly, both EtOH and C rats presented a similar lipid profile, which contrasts with other reports showing an increase in serum triglycerides (TG) and LDL, but not cholesterol, in adult rats treated during 4 wk with a 20% EtOH solution (Ojeda and others 2008) or 10 wk with a RW solution with 8% EtOH (Daher and others 2006). On the other hand, there seems to exist a general view that moderate wine consumption has a global cardioprotective effect in what concerns the metabolism of lipids.…”
Section: Resultscontrasting
confidence: 92%
“…The results of biochemical assays depicted in Table 2 demonstrated that in RW‐treated rats, the plasma levels of triglycerides, total cholesterol, and HDL were increased but without statistical significance, when compared to C group. Interestingly, both EtOH and C rats presented a similar lipid profile, which contrasts with other reports showing an increase in serum triglycerides (TG) and LDL, but not cholesterol, in adult rats treated during 4 wk with a 20% EtOH solution (Ojeda and others 2008) or 10 wk with a RW solution with 8% EtOH (Daher and others 2006). On the other hand, there seems to exist a general view that moderate wine consumption has a global cardioprotective effect in what concerns the metabolism of lipids.…”
Section: Resultscontrasting
confidence: 92%
“…This HT results from an increased production of large VLDL particles by the liver, while the splanchnic extraction of TG from chylomicron- and VLDL-remnants is secondarily enhanced. In another rat experiment, Daher et al confirmed a rise in plasma triacylglycerol and chylomicron concentrations after ethanol ingestion but also found a decreased chylomicron size with a change in cholesterol and phospholipid content indicating enhanced liver bile secretion [8]. In case the animals were put on a moderate alcohol diet for a period of ten weeks, their postprandial HT and hyperchylomicronemia were less pronounced.…”
Section: Alcohol and Triglycerides In Animal Studiesmentioning
confidence: 99%
“…Under preprandial conditions, high levels of apoB-containing lipoproteins like LDL make individuals prone to CVD. Under postprandial conditions, levels of apoB-containing lipoproteins increase, [42][43][44] and variations in subclasses of these lipoproteins are even greater when lipoprotein lipase is associated to apoB. 45 The rapid postprandial increase in triglyceride-rich lipoproteins (containing apoB100 and apoE) of normal individuals is increased in diseases related to arterial disease eg, diabetes mellitus, 46 and myocardial infarction.…”
Section: P38mentioning
confidence: 99%